A Look at Oral Cancer – Specifically Tongue Cancer - Ionmhain, Una nic (Trinity Student Medical Journal, 2007)
Oral cancers are defined as neoplasms arising between, and including, the lips and the anterior pillar of the fauces. Ninety percent of carcinomas arising in this region are squamous cell carcinomas1. These cancers are managed in differently depending on their staging and location. Many are silent lesions, presenting at a late stage, making treatment difficult and resulting in a low survival rate with this form of cancer. It is very rare in the West, with over 4500 cases diagnosed a year in the UK2, in contrast with Asia where it accounts for up to 40% of cancers3. Treatment is either surgical or radiotherapeutic, depending on the staging of the tumours. Prognosis is significantly worse in later stages, with a 45% to 65% survival rate when metastatic nodes in the neck are present4.